A Visual Two-Choice Rule-Switch Task for Head-Fixed Mice - Biró, Szabolcs; Lasztóczi, Bálint; Klausberger, Thomas (Frontiers in Behavioral Neuroscience, 2019)
Cognitive flexibility is the innate ability of the brain to change mental processes and to modify behavioural responses according to an ever-changing environment. As our brain has a limited capacity to process the information of our surroundings in any given moment, it uses sets as a strategy to aid neural processing systems. With assessing the capability of shifting between task sets, it is possible to test cognitive flexibility and executive functions. The most widely used neuropsychological task for the evaluation of these functions in humans is the Wisconsin Card Sorting Test, which requires the subject to alter response strategies and use previously irrelevant information to solve a problem. The test has proven clinical relevance, as poor performance has been reported in multiple neuropsychiatric conditions. Although, similar tasks have been used in pre-clinical rodent research, many are limited because of their manual-based testing procedures and their hardware attenuates neuronal recordings. We developed a two-choice rule-switch task whereby head-fixed C57BL/6 mice had to choose correctly one of the two virtual objects presented to retrieve a small water reward. The animals learnt to discriminate the visual cues and they successfully switched their strategies according to the related rules. We show that reaching successful performance after the rule changes required more trials in this task and that animals took more time to execute decisions when the two rules were in conflict. We used optogenetics to inhibit temporarily the medial prefrontal cortex (mPFC) during reward delivery and consumption, which significantly increased the number of trials needed to perform the second rule successfully (i.e., succeed in switching between rules), compared to control experiments. Furthermore, by assessing two types of error animals made after the rule switch, we show that interfering with the positive feedback integration, but leaving the negative feedback processing intact, does not influence the initial disengagement from the first rule, but impedes the maintenance of the newly acquired response set. These findings support the role of prefrontal networks in mice for cognitive flexibility, which is impaired during numerous neuropsychiatric diseases, such as schizophrenia and depression.